Influence of water quantity on the yield, water use efficiency, and plant water relations of Leucaena leucocephala in arid and semi arid environment using drip irrigation system (International Journal of Irrigation and Water Management, 2017)
Water is considered an important factor in the arid and semi-arid areas because water shortage affects the agricultural production. The current study aimed to investigate the influence of water application level on the dry matter yield, water use efficiency (WUE), and plant water status in Leucaena leucocephala. The treatments consisted of five levels of water applications based on actual evapotranspiration (AET): 0.25, 0.50, 0.75, 1.00 and 1.25 AET respectively. The production was increased from 306.4, 676.3, 724.1, 838.5, to 1172.7 kg/ha as the water application levels increased. The estimated WUE was 2.32, 2.57, 1.83, 1.59 and 1.78 kg/ha/mm for 0.25, 0.50, 0.75, 1.00 and 1.25 AET, respectively. Increasing the water application level did not increase the WUE. Using the irrigation level at 0.50 AET can be used to irrigate Leucaena crop without leaving any significant change in dry matter yield compared with 0.75 and 1.00 AET, respectively. There was no significant effect of water application level on each of the leaf water potential (Ψw) and leaf relative water content (LRWC). The means of Ψw was -2.3, -2.1, -2.2, -2.3, -2.2 MPa at 0.25, 0.50, 0.75, 1.00 and 1.25 AET, respectively. The means of leaf relative water content were 75, 74, 77, 77 and 78% at the water treatment levels, respectively. Under different water application levels, a poor correlation between the Ψw and LRWC existed. It is recommended to use 50% of AET as the best irrigation water management treatment for Leucaena production.